Approaches to the Cataract: Butor's Niagara - Elinor S. Miller (Studies in 20th & 21st Century Literature, 1977)
Michel Butor's 6 810 000 litres d'eau par seconde bears certain similarities to each of his earlier stereophonic works, but is much more than a reworking of established techniques. Generally thought to be difficult, as indicated by the title, which arouses interest without revealing the subject matter, the work has a complex and masterful structure. Against a background of gradually accelerated time, emphasized by appropriate sound effects, an Announcer leads a tour of Niagara Falls. Alphabetically identified characters play out predictable roles as newlyweds, second honeymooners, and the lonely ones. A Reader recites throughout Chateaubriand's classic description of the Falls, constantly recombining the original words in canon form. The initially forbidding typography with three typefaces and three margins creates the possibility of multiple readings. Each part is preceded by directions enabling the reader to alter the text, increasing the volume for some characters, drowning out others. Thus, theoretically, one could read any one of ten texts: "mobile readings," revealing each a different work. This mobility, with the typography, creates an "intellectual chord," not possible otherwise except in music. The subtly colored polyphonic mobile brilliantly serves to express Butor's view of the human condition, reflected in his stereophonic vision of the Falls.
Keywords: Michel Butor